Colistin: an Antibiotic and Its Role in Multiresistant Gram-negative Infections - Tonny Loho; Anti Dharmayanti (Acta Medica Indonesiana)
Increasing number of infection cases caused by multiresistant Gram-negative bacteria or multidrug resistant organism (MDRO) has become a major problem worldwide since there have been a lot of resistance to many classes of antibiotics. Mutant isolates such as fluoroquinolone-resistant and β-lactamase-resistant bacteria have been commonly found, particularly in intensive care unit (ICU). During the last two decades, there has been no study of developing antibiotics in search of discovering new type of antibiotics; meanwhile, the resistance of Gram-negative bacteria or MDRO to antibiotics is increasing. Colistin or polymyxin E is an old antibiotic, which has been used since 1959 for treating infection caused by Gram-negative MDRO. It was revealed that colistin has side effects of nephrotoxicity and neurotoxicity; therefore, the use of this antibiotic was stopped and it was replaced by other antibiotics which were effective and were considered safer at that time. There is an increasing number of infections with multi-resistant Gram-negative (MDRO) against the available antibiotics and the availability of alternative antibiotics has not been satisfying; therefore, microbiologists are searching back to the old option, which has been proven to be effective against multi-resistant Gram-negative bacteria, the old antibiotic that has been long forgotten, i.e. colistin, as an alternative treatment against Gram-negative MDRO. It is expected that colistin may have essential and reliable role as future antibiotics for treatment of multi-resistant Gram-negative infections and as an alternative of antibiotics that have been available so far. Key words: antibiotics, colistin, Gram-negative, multidrug resistant organism (MDRO).